2020
DOI: 10.1017/ipm.2020.38
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of meditation and mindfulness practices during times of crisis such as COVID-19

Abstract: Meditation and mindfulness are practices that can support healthcare professionals, patients, carers and the general public during times of crisis such as the current global pandemic caused by Covid-19. While there are many forms of meditation and mindfulness, of particular interest to healthcare professionals are those with an evidence base such as Mindfulness-Based Stress Reduction (MBSR). Systematic reviews of such practices have shown improvements in measures of anxiety, depression and pain scores. Structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
174
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(194 citation statements)
references
References 15 publications
10
174
0
10
Order By: Relevance
“…During the early stages of the Covid-19 epidemic, many researchers reported the need to provide interventions to support the mental health of people affected by the Covid-19 crisis [ 15 , 16 , 19 , 87 , 88 ], in particular for healthcare workers [ 18 , 89 , 90 , 91 ] and patients with the Covid-19 infection [ 92 , 93 ]. For this purpose, many scholars suggested the use of mindfulness interventions [ 94 , 95 , 96 , 97 ]. However, studies assessing the impact of interventions that supported mental health in the early stages of the Covid-19 related crisis are very limited.…”
Section: Discussionmentioning
confidence: 99%
“…During the early stages of the Covid-19 epidemic, many researchers reported the need to provide interventions to support the mental health of people affected by the Covid-19 crisis [ 15 , 16 , 19 , 87 , 88 ], in particular for healthcare workers [ 18 , 89 , 90 , 91 ] and patients with the Covid-19 infection [ 92 , 93 ]. For this purpose, many scholars suggested the use of mindfulness interventions [ 94 , 95 , 96 , 97 ]. However, studies assessing the impact of interventions that supported mental health in the early stages of the Covid-19 related crisis are very limited.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that health professionals could provide tailored and practical suggestions for the general population by targeting mood symptoms through exercise as a prevention or as a treatment strategy. Researchers have proposed to use mindfulness-based stress reduction practices to improve mental health during the COVID-19 [64][65][66]. In the current literature, mindfulness-based interventions have shown effectiveness in reducing anxiety and depression [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the fear associated with pandemic aligns with the preoccupation about the future whether the individual or his/her loved ones contract with the virus and develop the COVID-19 disease. On the contrary, mindfulness conveys the awareness and acception of the present moment that might allow individuals to be less overwhelmed by predominant symptoms such as anxiety, despair and depression that is present at the time of a global crisis (Behan, 2020). Thus, inverse association between the constructs are congruent.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, mindfulness was suggested as a useful skill that can offer a helpful way to adjust with such constant change and cope with anxiety and depression (Behan, 2020). Empirically, an immense number of studies demonstrated that increased levels of mindfulness is associated with decreased levels of anxiety and depression (Fong &Ho, 2020;Li et al, 2020;MacDonald & Olsen, 2020;Makadi & Koszycki, 2020;Montero-Marin et al, 2020;Soo, Kiernan&Anderson, 2020).…”
Section: Discussionmentioning
confidence: 99%